Two Problems in the Old Testament Examined in the Light of Assyriology - Driver, G. R.
1. The provision for Joseph’s family in Egypt (Gen 47: 12-17) — 2. The “Waters of Bitterness” (Numbers 5:11-28) — 3. A prohibition to sell hereditary property (Deut. 18:8).